Severe chest trauma: diagnostic and therapeutic bases - Cazabán, Luis A; Bergalli, Luis E (Cirugía del Uruguay, 1974)
The authors' experience with severe thoracic traumatisms totals 27 cases, out of which 6 clinical cases have been selected for the purpose of this paper. Only 3 of these survived. Physiopatho]ogical considerations ( alteration of ventilation caused by pain and secretions, perfusion due to apneumatic foci or arterio-venous shunts), are discussed on the basis of fundamental clinical and functional parameters. To this should be added fall of heart function and direct heart contusion. Direct effect is shock's lung syndrome and diffuse broncho-alveolar pulmonary obstruction. Cases are divided according to their clinical pattern into the following categories: severe thoracic traumatisms with tissue hipoperfusion; severe thoracic traumatisms with alveolar hipoventilation; co-existance of above conditions or with multiple arterio-venous ;hunts. These patients should be considered as cases of trunk traumatisms and diagnostica! means directed to eliminating associated lesions should be exhausted. Treatment should be on the premise that the seriousness of the condition will prevent any treatment deferred to a second stage. Consequently we find majar and minor therapeutic procedures, among which are considered as· specially valuable and fundamental urgency thoracotomy, osteosynthesis, bronchospiration and internal pneumatic stabilization.